2003
DOI: 10.1128/aac.47.4.1308-1312.2003
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activities of Methoxyfluoroquinolones Gatifloxacin and Moxifloxacin against Aerobic and Anaerobic Respiratory Pathogens in Serum

Abstract: Gatifloxacin (Bristol-Myers Squibb) and moxifloxacin (Bayer) are new methoxyfluoroquinolones with broadspectrum activity against aerobic and anaerobic pathogens of the respiratory tract. In this investigation, we analyzed the bactericidal activity in serum over time of these antimicrobials against three aerobic (Streptococcus pneumoniae, Haemophilus influenzae, and Staphylococcus aureus) and four anaerobic (Peptostreptococcus micros, Peptostreptococcus magnus, Fusobacterium nucleatum, and Prevotella melaninoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…Conversely, cidal moxifloxacin activity was found for respiratory pathogens (aerobes and anaerobes) even when sera were obtained 24 h after dosing. The results suggest that moxifloxacin may have clinical utility in the treatment of mixed aerobic/anaerobic respiratory tract infections (Stein et al, 2003b). In a recently published paper investigating serum bactericidal activity of moxifloxacin and gatifloxacin, Stein et al (2003a) reported little or no serum bactericidal activity of either drug if the MICs of gatifloxacin were >2 mg l À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, cidal moxifloxacin activity was found for respiratory pathogens (aerobes and anaerobes) even when sera were obtained 24 h after dosing. The results suggest that moxifloxacin may have clinical utility in the treatment of mixed aerobic/anaerobic respiratory tract infections (Stein et al, 2003b). In a recently published paper investigating serum bactericidal activity of moxifloxacin and gatifloxacin, Stein et al (2003a) reported little or no serum bactericidal activity of either drug if the MICs of gatifloxacin were >2 mg l À1 .…”
Section: Introductionmentioning
confidence: 99%
“…The methoxyfluoroquinolones, gatifloxacin and moxifloxacin, have in vitro potency similar to that of trovafloxacin against a broad spectrum of anaerobic bacteria and appear to have the potential to treat mixed aerobic and anaerobic infections [12][13][14]. Moxifloxacin recently received approval from the US Food and Drug Administration for the treatment of complicated skin or skin-structure infections and complicated intra-abdominal infections.…”
mentioning
confidence: 97%
“…We used conditional logistic regression to estimate the odds ratio for the association between C. difficile-associated disease and previous treatment with the various fluoroquinolones, using levofloxacin exposure as the reference category. The two comparison groups were gatifloxacin and moxifloxacin (combined because the number of cases was smaller than expected and because of their similar antimicrobial activity) (17,29) and ciprofloxacin.…”
mentioning
confidence: 99%